EMOJIS: NEW LANGUAGE OR TECHNOLOGY-BASED TREND? - Danesi, Marcel (ETC: A Review of General Semantics)
The article examines weather emoji writing constitute a new visual language, communicating through the eye rather than through the ear. It evaluates actual text messages and tweets written by students in their early twenties and synthesizing previous ideas regarding emojis as more than just a pictographic-ideographic writing system, complementing alphabetic writing and, in some contexts, substituting it completely. It also informs on future of writing, literacy, and consciousness.